Puccini's Il trittico : Il tabarro, Suor Angelica, Gianni Schicchi - Fisher, Burton D.; Adami, Giuseppe, 1878-1946; Adami, Giuseppe, 1878-1946; Forzano, Giovacchino; Forzano, Giovacchino; Forzano, Giovacchino; Forzano, Giovacchino; Puccini, Giacomo, 1858-1924 (Opera classics library., 2002)
A comprehensive guide to Puccini's IL TRITTICO (IL TABARRO, SUOR ANGELICA, GIANNI SCHICCHI), featuring Brief Story Synopsis, Principal Characters, Story Narrative with Music Highlight Examples, a complete, newly translated libretto of each opera with Italian/English translation side-by-side, an in depth and insightful Commentary and Analysis, a Discography, Videography and Dictionary of Opera and Musical terms.